Study of the flexural behaviour of FRP-strengthened steel-concrete composite beams. (December 2019) - Stylianidis, P.M.; Petrou, M.F.
Abstract: Flexural strengthening of steel-concrete composite beams with fiber-reinforced polymer (FRP) materials has recently become a topic of considerable interest, due to the many advantages it may offer in both enhancing the design prospects of new structures and restoring the functioning condition of deficient existing structures. During the past two decades, a substantial number of experimental, numerical and analytical studies has been concerned with this topic. Although these studies have provided significant insights into the problem, a lack of simplified methods for assessing the FRP-strengthening effects in a quantitative manner still exists. Motivated by this need, a study that seeks to establish a sound understanding of the mechanics of the problem – which is a fundamental component for the development of simple and reliable analysis approaches – is presented in this paper. The basis of the study is the development of a new analytical method for the prediction of the moment-curvature relationship and the overall flexural response of FRP-strengthened steel-concrete beams, by assuming perfect bond between the constitutive components. The method only requires accessible spreadsheet calculations, which makes it both suitable for routine use in design practice and particularly useful for the scientific study of the problem. The new method is first validated against available experimental results and it is then employed in conducting a systematic parametric study, from which several conclusions of essential practical significance for the optimum use of FRP composites in strengthening the flexural behaviour of steel-concrete composite beams are derived.